FATORES RELACIONADOS COM A OCORRENCIA E EVOLUCAO DAS ENDOFTALMITES - Schellini, Silvana Artioli [UNESP]; Marotti Junior, J. V. [UNESP]; Shigueru Tomita, S. [UNESP]; Silva, Maria Rosa Bet de Moraes [UNESP] (My University, 1996)
We retrospectively analysed 33 endophthalmitis patients treated at the Faculdade de Medicina de Botucatu. We observed that 81,8% of these patients were males and older than 60 years. Trauma was the main cause of endophthalmitis (42,4%). Endophthalmitis severity can be assessed by the fact there was no improvement on the final visual acuity.
Factor related to the occurrence and evolution of endophthalmitis
Keywords: endophthalmitis; intraocular infection; amikacin; antibiotic agent; cephalosporin derivative; gentamicin; penicillin derivative; tobramycin; clinical article; disease course; disease severity; female; human; injury; male; visual acuity